The teacher's sense of plausibility revisited - Alan Maley (Universitas Katolik Indonesia Atma Jaya, 2016)
My aim is to give substance to Prabhu’s (1987) concept of ‘the teacher’s sense of plausibility’. That is to say, explore the way teachers develop professionally and personally by building a personal theory of teaching action based upon their own accumulated experiences - and reflection on them. Objective history is useful but perhaps more interesting are our personal histories. In this paper I shall attempt to link my own personal history in ELT to the places I have worked in, to the personalities I have encountered, to the evolving currents of ideas and publications, and to key critical moments in my own development. I shall weave together the five strands of places, personalities, ideas, publications and critical moments to demonstrate how they have influenced the direction of my own continuing development of a personal ‘theory’ of teaching. I shall suggest that this kind of reflective process can be a valuable element within the framework of teacher development as a whole.